2017
DOI: 10.1002/adfm.201604423
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Crosslink Method for a Straightforward Synthesis of Poly(Vinyl Alcohol)‐Based Aerogel Assisted by Carbon Nanotube

Abstract: As a new concept, a self‐crosslink mechanism for hydrothermal synthesis of poly(vinyl alcohol) (PVA) aerogel, assisted by multiwall carbon nanotubes, is reported. PVA, working as a low‐cost and commercially available raw material, exempts the complicated synthesis process and reserves its nontoxic nature since no organic crosslinkers are used in the synthesis process. The crosslink density and many other properties of the products can be easily tuned by simply altering the concentration of PVA precursors, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…[7] Their absorption capacity is also higher than that of poly(vinyl alcohol)-based aerogels with the similar bulk density (25-85 mg cm À3 )probably because they are more swollen and expand their volumes during absorption process. [28] When the amount of VMDMS in the precursors is further increased, PVPDMS-based copolymer aerogels with different microstructures and physical properties from those of PA 1 and PA 2c an be obtained via APD.W ith the molar ratio of VDMMS to VMDMS decreasing to 1:1a nd 1:2, the macroscopic phase separation is further suppressed by the network with lower hydrophobicity and higher cross-linking density, leading to am icrostructure with smaller particle and pore sizes (Figure 3a-c and Figure S4). Theparticle and pore sizes of PA 3are 35-100 and 30-180 nm, respectively,while those of PA 4a re 20-80 and 20-100 nm, respectively.B ecause of the abundance of nanosized particles and pores,P A3 and PA 4 exhibit high SSAs of 438 and 605 m 2 g À1 ,respectively.Due to homogeneity of the nanostructure,P A4 becomes even translucent with visible-light transmittance of 67 %a tw avelength of 550 nm for 1mmt hick sample (Figure 3h).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[7] Their absorption capacity is also higher than that of poly(vinyl alcohol)-based aerogels with the similar bulk density (25-85 mg cm À3 )probably because they are more swollen and expand their volumes during absorption process. [28] When the amount of VMDMS in the precursors is further increased, PVPDMS-based copolymer aerogels with different microstructures and physical properties from those of PA 1 and PA 2c an be obtained via APD.W ith the molar ratio of VDMMS to VMDMS decreasing to 1:1a nd 1:2, the macroscopic phase separation is further suppressed by the network with lower hydrophobicity and higher cross-linking density, leading to am icrostructure with smaller particle and pore sizes (Figure 3a-c and Figure S4). Theparticle and pore sizes of PA 3are 35-100 and 30-180 nm, respectively,while those of PA 4a re 20-80 and 20-100 nm, respectively.B ecause of the abundance of nanosized particles and pores,P A3 and PA 4 exhibit high SSAs of 438 and 605 m 2 g À1 ,respectively.Due to homogeneity of the nanostructure,P A4 becomes even translucent with visible-light transmittance of 67 %a tw avelength of 550 nm for 1mmt hick sample (Figure 3h).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However,t raditional aerogels are usually dried via costly supercritical drying (SCD) and exhibit low mechanical strength because of their intrinsically fragile/brittle networks,w hich need to be addressed before their practical applications.To overcome the costly drying process and brittleness, many efforts have been made to lower the cost by ambient pressure drying (APD), [23] freeze drying (FD) [22] and vacuum drying (VD), [24] and reinforce the aerogels by av ariety of methods.C ross-linking of aerogels with organic polymers is aw idely used method to reinforce the aerogels but usually results in lower porosity and higher density that limit their applications. [25,26] Flexible polymer-based aerogels can be obtained from resorcinol-formaldehyde, [27] poly(vinyl alcohol), [28] and supramolecules, [29] and some of them exhibit good absorption of organic solvents/oils.A nother kind of aerogels based on biomass such as nanocellulose and chitosan with compressibility and bendability have been reported. [30,31] Owing to their highly porous nanostructure that is composed of nanofibers,t hey show excellent thermal insulation performances.B esides,a ssembly of nanofibers via as pecific method can give compressible and elastic cellular aerogels with high pressure-sensitivity and good absorption/separation properties.…”
mentioning
confidence: 99%
“…When used as adsorbent for selective oil/water separation, the adsorption capacity was higher than 100 times its own weight. Carbon nanotubes are emerging as a simple 1D material with excellent hydrophobicity and high surface area, and the CNTs aerogels are also familiarized with people as a selective adsorbent for organic pollutants , . For example, Gui et al reported a magnetic CNTs aerogel with a high mass sorption capacity for diesel oil with 56 g g ‐1 .…”
Section: Applications Based On Adsorption Performancementioning
confidence: 99%
“…Moreover, CNTs were added to the graphene aerogel to improve the mechanical strength and specific surface area. The composite aerogels are more suitable for environmental clean‐up, especially for oil/water separation , , , . Zhan et al creatively introduced PDA‐functionalized carbon nanotubes into graphene aerogel to form a robust PDA/MWCNT/graphene composite aerogel with a novel “cabbagelike” hierarchical porous structure ( Figure ) .…”
Section: Applications Based On Adsorption Performancementioning
confidence: 99%
“…They are typically prepared by a sol-gel process to obtain hydrogels or alcogels followed by a specific drying process to replace the liquid solvent with air without destroying their delicate nanostructure. Due to their unique porous structures, many kinds of aerogel possess high specific surface area (SSA) and low thermal conductivity, which make them attractive as thermal superinsulators, 1,2 adsorbents, 3,4 catalyst supports, 5 energy storage materials, [6][7][8] etc. Because of their homogeneous nanostructure, some aerogels, especially silica aerogels, are transparent in the visible light wavelengths, which makes them ideal materials as thermally superinsulating windows for efficient energy savings in houses and buildings.…”
Section: Introductionmentioning
confidence: 99%